Financial Performance Analysis at PT. Bank Rakyat Indonesia (PERSERO) Tbk - Marvel Poppy Sabarhati Waruwu; Karona Cahya Susena; Rinto Noviantoro (Journal of Indonesian Management, 2021)
This study aims to determine the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk in 2019. The analysis method used is financial ratio analysis, namely Cash Ratio (CR), Short Term Mistmatch (STM), Return On Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR). The research results prove that the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk, using the 2015 cash ratio (CR) of 17.15%, in 2016 of 14.58%, 2017 of 12.34% in 2018 of 14.21% and in 2019 of 12 , 76%, this indicates that the value of the large cash ratio (CR) is 4.80, which means the financial performance of PT. Bank Rakyat Indonesia (Persero) Tbk is included in the very healthy criteria and is in the 1st rank, which is more than 4.80, which means that PT. Bank Rakyat Indonesia (Persero) Tbk is able to solve liquidity problems in the company. Short Term Miscmatch (STM) PT. Bank Rakyat Indonesia (Persero) Tbk in 2015 amounted to 155%, 2016 amounted to 189%, 2017 amounted to 168%, 2018 amounted to 196% and in 2019 amounted to 196% included in very healthy criteria and in rank 1, because the total ratio greater (>) than 110%. Return on Assets (ROA) of PT. Bank Rakyat Indonesia (Persero) Tbk in 2015 amounted to 3.7%, in 2016 amounted to 3.38%, in 2017 amounted to 3.29, in 2018 amounted to 3.21% and in 2019 amounted to 3.06% and is included in the very good criteria. Net Interest Margin (NIM) of PT. Bank Rakyat Indonesia (Persero) Tbk in 2015 was 10.31%, 2016 was 10.50%, 2017 was 10.15%, 2018 was 9.47% and 2019 was 9.31% included in the very healthy criteria each of which results from 2015, 2016, 2017, 2018, up to 2019 are ranked 1. Capital Adequacy Ratio (CAR) PT. Bank Rakyat Indonesia (Persero) Tbk in 2015 was 28%, 2016 was 24%, 2017 was 22%, 2018 was 18% and 2019 was 16%. to 2015, 2016, 2017, 2018 and 2019 are in 1st rank.